THE EFFECT OF DISCOVERY LEARNING ASSISTED BY ELECTRONIC MODULES (E-MODULES) ON STUDENTS’ CRITICAL THINKING SKILLS IN VIRUS TOPIC OF GRADE X AT SMA NEGERI 9 PEKANBARU - Meiandreas, Faisal; Darmadi; Natalina, Mariani (Yayasan Amanah Nur Aman, 2026)
Twenty-first century science learning requires students to possess critical thinking skills; however, in practice, students still experience difficulties in understanding complex biological concepts, particularly virus material, which is abstract and microscopic in nature. This condition has an impact on the low achievement of critical thinking indicators at SMA Negeri 9 Pekanbaru. This study aims to determine the effect of the Discovery Learning model assisted by electronic modules (e-modules) on students’ critical thinking skills and to describe the improvement of critical thinking ability in each indicator. The research employed a quantitative method with a quasi-experimental design using a pretest–posttest control group design. The research sample consisted of two classes: class X.3 as the experimental group and class X.2 as the control group, each comprising 37 students. The experimental group implemented Discovery Learning assisted by e-modules, while the control group applied Discovery Learning without e-modules. Data were collected through pretests, posttests, and critical thinking observation sheets, and then analyzed using normality tests, homogeneity tests, t-tests, and N-Gain tests. The results showed that the average posttest score of the experimental group (84.46) was in the critical category and higher than that of the control group (69.17). The average N-Gain value of the experimental group was 71.3%, categorized as moderately effective, while the control group achieved 48.7%, categorized as less effective. Hypothesis testing indicated a significance value of 0.000 < 0.05, confirming that Discovery Learning assisted by e-modules has a significant effect and is more effective in improving students’ critical thinking skills on virus material.